A HERMENEUTIC APPROACH TO SPATIAL REFLECTIONS IN CIHAN AKTAŞ’S NOVEL ŞIRIN’S WEDDING - GÜZEL, Mahbube (Atlas Journal, 2022)
Many Studies have been conducted in different disciplines on what the concep of space, which constitues an important branch of literary texts, can be. In these studies, whether the concept of space is a place that can be perceived abstractly or whether it covers human experience has been examined with different methods and approaches. Places loaded with value with the presence of people completely surround people. In this context, the space where our existence gains meaning is also a space of experience. For example, Gadamer says that space is “encompassing everything that exists in space.” (Gadamer, 2008) This thing includes people and objects. Therefore, spaces are an area of interaction and experience. Based on this idea, based on Gadamer’s argument, it will be examined that space is not independent of human experience amd Cihan Aktaş’s novel “Sirin’s Wedding” will be evaluated in terms of space-human relationship